Caminhos metodológicos para uma leitura de suplementos infantis - Porto, Sérgio Dayrell (Cadernos de Linguagem e Sociedade, 2010)
This paper can be useful and revealing of the methodological avenues of the research ’Propositions for a children’s paper’, suppported by the CNPq and developed by the University of Brasília. Such a methodology can be summed up as the interpretation of children’s supplements (children’s papers) enclosed in leading Brazilian newspapers. Our hypothesis was that these little papers make up an adult’s reading, although they are dressed up with children’s themes. The hypothesis was confirmed by means of a linguistic-qualitative methodology with theoretical support from French-oriented discourse analysis, institutional analysis and Lacanian semiology.